Schubert, Müller, and Die schöne Müllerin - Youens, Susan (Cambridge Cambridge University Press, 1997)
The collaboration of Schubert and the poet Wilhelm MÜller produced some of the best loved of nineteenth-century lieder--in particular Die schöne MÜllerin. Professor Youens shows how this archetypal tale of love and rejection is reflected in the poet's own experience. She considers other poets' explorations of the subject, and looks at other musical settings of MÜller's mill poems. Above all she examines MÜller's permutation of the literary legends as an exploration of erotic obsession, delusion, frenzy, disillusionment and death and the way in which Schubert altered MÜller's vision when the poetic cycle became a musical text.